(untitled) (Colombia Medica, 1986)
This catalog of 88 Culicoides species in Colombia is based on the identification of specimens from the reference collection of the Departamento de Microbiología, Facultad de Salud, Universidad del Valle, Cali, Colombia, and existing literature on the geographical distribution of this genus.